Research on the Impact of Duty-free Policy on Hainan Outlying Islands - Liu Yihan (SHS Web of Conferences)
Hainan Province’s unique geographical advantages are in an important position in China’s future economic development layout. Promote the development Hainan Province’s economy tourism, The State promulgated the offshore duty-free policy in Hainan Province, and paper studies impact on the tourism consumption and economic development Hainan Province in this context. The results show that the impact of the offshore duty-free policy on tourism consumption and economic development in Hainan Province has increased significantly, implementation of the duty-free policy has also led development surrounding industries. Conclusion that the offshore duty-free policy has stimulated tourism consumption and economic development in Hainan Province is valid in the short term. At present, based on the content of the policy, this paper will further expand the duty-free quota and commodity categories of duty-free goods, and strengthen the improvement and publicity of the policy, so as to build a world-class international shopping center and international tourism center.